2002
DOI: 10.1007/bf02376052
|View full text |Cite
|
Sign up to set email alerts
|

The detection of hydrogen in molten aluminium

Abstract: Abstract. The presence of hydrogen in aluminium poses problems to the foundry and casting industries, because high residual hydrogen contents in molten aluminium cause significant porosity in the solid aluminium after casting. This usually renders the product useless as it may fail mechanically. Therefore, fast, accurate and reliable techniques are required for monitoring the dissolved hydrogen content in molten aluminium, but this particularly harsh environment places considerable restrictions on the equipmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Another important matter is the presence of round-shape gas pores which have the average diameter less than 10 µm. An intensive attraction of environmental gases occurred for this sample at 850 °C for aluminum alloys [29,30] and it seems that these round-shape small pores are not related to gas entrapment due to very low viscosity of the melt [31,32]. Like the other samples, agglomeration of ceramic particles could be observed for this sample.…”
Section: -1-sem and Om Studies Of The Composite Microstructuresmentioning
confidence: 77%
“…Another important matter is the presence of round-shape gas pores which have the average diameter less than 10 µm. An intensive attraction of environmental gases occurred for this sample at 850 °C for aluminum alloys [29,30] and it seems that these round-shape small pores are not related to gas entrapment due to very low viscosity of the melt [31,32]. Like the other samples, agglomeration of ceramic particles could be observed for this sample.…”
Section: -1-sem and Om Studies Of The Composite Microstructuresmentioning
confidence: 77%
“…(iv) also, the system performed better with a slower steam flow rate; a curve of best fit would indicate a drastic increase in the hydrogen evolution percentage, as the steam flow rate decreased Wang et al 43 a review on hydrogen production using aluminum and aluminum alloys in this article, researchers conducted a review of hydrogen production by using aluminum and aluminum alloys; the review study was compartmentalized according to the current status of hydrogen production, background information about the use of alloys to produce hydrogen, and the limitations associated with commercialization (i) the article verifies that aluminum−water chemical reactions are usually conducted in neutral and alkaline conditions. (ii) the article also asserts that processes such as ball milling and metal doping can be highly effective processes to optimize the reaction Lapham et al 44 the detection of hydrogen in molten aluminum (i) due to hydrogen's solubility within molten aluminum, researchers conducted a study to identify the various techniques that can be used to detect hydrogen within molten aluminum. (ii) this research holds great relevance due to the fact that as aluminum decreases in temperature hydrogen bubbles form within the aluminum, causing porosity to occur; the pores that formed within an aluminum sample can be considered detrimental in regards to the structural integrity of a part going through the casting process.…”
Section: Potential Environmental Impact and Scalabilitymentioning
confidence: 99%
“…[1][2][3] Previous research showed that inclusions, mainly of aluminum oxide, had a close correlation with the hydrogen content in aluminum melt. [4][5][6][7] Specifically, aluminum oxide inclusion usually increases with a higher level of hydrogen content. The major aluminum oxide inclusion in molten aluminum is an oxide film that results from the reaction between molten aluminum and water vapor in the air.…”
Section: Introductionmentioning
confidence: 99%